Implications of Interpersonal Conflict for Physicians’ Task Performance: Workplace Deviance as a Mediator - sulaksono, Andri; Burhan Bungin; Liliana Dewi; Alexander Hiro Wibisono (MATRIK: JURNAL MANAJEMEN, STRATEGI BISNIS, DAN KEWIRAUSAHAAN, 2026)
Medical environments frequently encounter interpersonal tensions that influence clinical effectiveness and may shape how physicians carry out their tasks. Grounded in Social Exchange Theory and Conservation of Resources Theory, this study examines the link between interpersonal conflict and physicians’ task performance by considering workplace deviance as a mediating mechanism. Using a cross-sectional design and surveyed a population of physicians in various healthcare facilities in Surabaya. Using purposive sampling than collected data from 150 respondents via an online, self-administered structured questionnaire. The data were analyzed with PLS-SEM. The measurement model met all reliability and validity criteria, and the structural model demonstrated significant explanatory and predictive power. The findings indicate that conflict can actually enhance performance when it is managed as task-focused disagreement within a framework of strong professional controls. In contrast, deviant behaviors consistently undermine performance. Furthermore, workplace deviance partially mediated the relationship between conflict and performance. Based on these findings, the study offers practical solutions for healthcare organizations in Indonesia. Include implementing effective conflict management, providing communication training, and consistently enforcing a code of ethics to harness potential benefits of task-related conflict.